Investigating the Association Between Traffic-related Air Pollution (PM2.5 and Benzene) and the Risk of Asthma: A Systematic Review and Meta-analysis - Maryam Nazari; Abdollah Mohammadian-Hafshejani; Mohsen Arbabi (Epidemiology and Health System Journal)
Background and aims: Asthma is a chronic disease that causes respiratory system inflammation. Recently, traffic-related air pollution (TRAP), especially particulate matter (PM2.5) and benzene, has been considered a factor that may increase the risk of asthma. This study investigated the association between TRAP (PM2.5 and benzene) and asthma risk. Methods: In this systematic review and meta-analysis, the relevant published data were collected by searching the Cochrane Library, Web of Science, ScienceDirect, Scopus, PubMed, and Google Scholar databases up to November 2022. The study quality was evaluated using the Newcastle-Ottawa Scale checklist. The data were analyzed using Stata software (version 14), and the significance level in this meta-analysis study was considered to be<0.05. Results: In the first search, 4,909 and 4,825 studies were extracted for PM2.5 and benzene, respectively. After evaluating and considering the search criteria, 25 and 4 studies remained for PM2.5 and benzene, respectively. For PM2.5, the odds ratio (OR) for developing asthma in the TRAP-exposed group compared to the unexposed group was 1.11 (95% confidence interval [CI]: 1.04-1.19, P=0.002). For benzene, the OR of developing asthma in the exposed group was 1.19 when compared to the unexposed group (95% CI: 1.10-1.29, P<0.001). Conclusion: Based on this review study, there was a positive association between TRAP exposure and the development of asthma. The results confirmed that PM2.5 and benzene increase the risk of asthma.